2022
DOI: 10.3390/su141811371
|View full text |Cite
|
Sign up to set email alerts
|

Interlinkage of Perceived Ecotourism Design Affordance, Perceived Value of Destination Experiences, Destination Reputation, and Loyalty

Abstract: The aim of this study is to analyse the relationships between the perceived ecotourism design affordances (PEDA), perceived value of destination experience (PERVAL), destination reputation, and destination loyalty among the tourists visiting Langkawi Island, Malaysia. It extends the affordance theory through the lens of Gestalt theory and ecological dynamics in understanding the interactions between tourists and products derived from their ecotourism environment. A quantitative approach was utilised, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…A high percentage of destinations still present limited brand awareness in terms of quality among potential tourists [36] who use the internet as their key source of information [37]. Social media platforms can contribute to a traveler's awareness process of different destinations [38].…”
Section: Sustainability and Tourism Destinationsmentioning
confidence: 99%
“…A high percentage of destinations still present limited brand awareness in terms of quality among potential tourists [36] who use the internet as their key source of information [37]. Social media platforms can contribute to a traveler's awareness process of different destinations [38].…”
Section: Sustainability and Tourism Destinationsmentioning
confidence: 99%
“…The third type of analysis revolves around examining the perception of affordances and how such perception influences tourist behavior. For instance, Azinuddin et al [34] conducted a survey on Langkawi Island and found that perceived design affordances significantly impact perceived value, which subsequently affects destination reputation and loyalty in ecotourism. Moreover, Borghini et al [54] revealed that sensory, symbolic, and cognitive affordances within a space evoke feelings of attachment or detachment among customers of their favorite stores.…”
Section: Affordance Theory In the Tourism Environmentmentioning
confidence: 99%
“…Firstly, it employs affordance theory within the context of tea tourism, addressing the call for tourism research that focuses on the tourism experience itself [28,59]. Affordance theory offers a fresh and insightful framework to comprehend how individuals perceive and interact with tourism environment affordance, highlighting the potential for action and the opportunities an environment presents [34,59]. By applying affordance theory to the analysis of tea tourism, this study illuminates the distinctive and multifaceted elements that tea tourists encounter at various tea tourism sites [12].…”
Section: Applying Affordance Theory In Tea Tourism Contextmentioning
confidence: 99%
See 2 more Smart Citations